2018
DOI: 10.1101/469395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A transcriptional cycle suited to daytime N2 fixation in the unicellular cyanobacterium Candidatus Atelocyanobacterium thalassa (UCYN-A)

Abstract: 27The symbiosis between a marine alga and a N 2 -fixing cyanobacterium (UCYN-A) is 28 geographically widespread in the oceans and is important in the marine N cycle. UCYN-A is 29 uncultivated, and is an unusual unicellular cyanobacterium because it lacks many metabolic 30 functions, including oxygenic photosynthesis and carbon fixation, which are typical in 31 cyanobacteria. It is now presumed to be an obligate symbiont of haptophytes closely related to 32 Braarudosphaera bigelowii. N 2 -fixing cyanobacteria u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Transcripts for most pathways in this diazotroph only showed a weak relationship or no significant positive correlation with the pathways in the other phytoplankton populations. However, this is in agreement with other culture [68] and field-based observations [15,69]. The process of N 2 fixation in this unicellular cyanobacteria seems to require a tightly orchestrated diel cycle distinct from other diazotrophs and nondiazotrophic microorganisms [15,69].…”
Section: Diel Oscillations Of Transcripts Involved In Photosynthesissupporting
confidence: 91%
“…Transcripts for most pathways in this diazotroph only showed a weak relationship or no significant positive correlation with the pathways in the other phytoplankton populations. However, this is in agreement with other culture [68] and field-based observations [15,69]. The process of N 2 fixation in this unicellular cyanobacteria seems to require a tightly orchestrated diel cycle distinct from other diazotrophs and nondiazotrophic microorganisms [15,69].…”
Section: Diel Oscillations Of Transcripts Involved In Photosynthesissupporting
confidence: 91%
“…Several mechanisms have been considered, such as its nitrogenase is confined to specialized cells called diazocytes (Bergman and Carpenter, 1991), the photoreduction of O 2 to H 2 O in the photosystem I (the Mehler reaction) (Milligan et al, 2007), the uncoupling of CO 2 and N 2 fixation in cyanophycin granules (Finzi-Hart et al, 2009), or the down-regulation of photosynthesis during the period of maximum nitrogenase activity at midday (Berman-Frank et al, 2001b), which suggests that light may also be a determinant factor for BNF. Interestingly, the symbiosis between UCYN-A (which lacks genes for oxygenic photosynthesis and C fixation, and its algal host has led to enable daytime BNF (Muñoz-Marín et al, 2018), although nifH expression of UCYN-A has also been observed at night (Moisander et al, 2014).…”
Section: Factors Affecting Bnf In Marine Systemsmentioning
confidence: 99%
“…Furthermore, in Crocosphaera and Cyanothece , the transcription of the shc gene peaks right before the nitrogenase-encoding gene ( nifH ) starts increasing its expression level (data collected from ref. 20), and simultaneous expression of both markers has also been detected in UCYN-A (21). These patterns are further supported by previous observations of hopanoid production in the cyanobacterium Crocosphaera watsonii WH8501 in the context of N 2 fixation (22, 23).…”
mentioning
confidence: 98%
“…Asterisk (*), experimentally tested in refs. 20 and 21 (n.t., not tested). Enzymes participating in hopanoid pathways: squalene−hopene cyclase (SHC), hopanoid biosynthesis-associated radical SAM protein (HpnH), hopanoid-associated phosphorylase (HpnG), hopanoid biosynthesis-associated glycosyltransferase protein (HpnI), hopanoid biosynthesis-associated protein (HpnK), hopanoid biosynthesis-associated radical SAM protein (HpnJ), aminotransferase (HpnO), hopanoid 2-methyltransferase (HpnP), and hopanoid C3 methylase (HpnR); 3-methylhopanoid production has never been found in marine cyanobacteria (28); hpnO was absent in all of the screened strains.…”
mentioning
confidence: 99%